Knowledge about and attitudes towards medical cannabis among Austrian university students. (May 2021) - Felnhofer, Anna; Kothgassner, Oswald D.; Stoll, Astrid; Klier, Claudia
Highlights: More than half of students said they learnt about medical cannabis at university. All students struggled to differentiate between CBD and THC. Chronic pain, oncological diseases and palliative care were the most frequently cited indications. Males were more positive about legalizing and prescribing cannabis than females. More females perceived cannabis as physically addictive and as a gate-way drug. Abstract: Background: The relevance of medical cannabis (MC) increases; and, educating those who are at the forefront of patient care is imperative. Yet, research on medical students' expertise and opinions is still scarce. Objective: This study set out to evaluate Austrian medical students' knowledge about and attitudes towards MC and compare them with other academic disciplines. Additionally, gender was controlled for. Methods: An online survey was conducted with N = 404 students enrolled in (1) medical studies, (2) studies with a medical background and (3) studies without a medical background. Results: In contrast to non-medical students, 64 % of medical students said they learnt about MC at the university. Although students were confident about their knowledge, they struggled to differentiate between CBD and THC. Chronic pain, oncological diseases and palliative care were the most frequently cited indications, psychiatric indications, however, were mentioned less often. Medical students were more reserved in their attitudes towards increasing medical usage and legalizing cannabis than the two other groups. Also, they were more skeptical about whether physicians should be allowed to prescribe MC and whether they should be obliged to offer it. Males showed more confidence regarding cannabis knowledge and were more favorable of legalizing and prescribing cannabis; females perceived cannabis as more physically addictive and as a gate-way drug. Conclusions: Considering that beliefs and attitudes shape behavior, it is expected that future health care professionals will struggle with recommending cannabis for medical treatment. A coordinated approach for medical training is needed to ensure high standard medical care.